MENGEMBANGKAN KREATIVITAS MENGGUNAKAN METODE COOPERATIVE SCRIPT DALAM PEMBELAJARAN TARI KREASI DI SMPN 1 PANDEGLANG - Deasari, Wulan; Permanasari, Alis Triena; Rizal, Syamsul (Yayasan Amanah Nur Aman, 2025)
This study explores the implementation of the Cooperative Script method in enhancing creativity through creative dance learning for Grade VIII A students at SMP Negeri 1 Pandeglang. The objective is to foster student creativity by integrating cooperative learning with artistic expression. The research uses a qualitative descriptive approach, involving observations, interviews, and documentation. The learning process was carried out in five stages: planning, group division, collaborative material discussions, mentoring, and final performance. The Cooperative Script method allowed students to actively engage in summarizing, presenting, exchanging roles, and creating original dance compositions based on the Rentak Rebana theme. Results show increased student enthusiasm, improved critical thinking, and stronger collaboration skills. Supporting factors included adequate school facilities, responsive student attitudes, and teacher guidance. However, challenges were identified, such as limited learning time and low initial interest, especially among male students. The application of this method proved effective in promoting student-centered learning, creative expression, and social interaction, aligning well with the curriculum’s goals. In conclusion, the Cooperative Script method is a valuable strategy in developing students’ creativity in cultural arts education, particularly in dance learning, by creating an interactive and meaningful learning environment.